IVIM-diffusion-MRI for the differentiation of solid benign and malign hypervascular liver lesions: evaluation with two different MR scanners - Klauß, Miriam; Mayer, Philipp; Maier-Hein, Klaus H.; Laun, Frederik B.; Mehrabi, Arianeb; Kauczor, Hans-Ulrich; Stieltjes, Bram (European journal of radiology, 2016)
Purpose - Hepatocellular carcinoma (HCC) and focal nodular hyperplasia (FNH) as the most common malign and benign liver tumors are both hypervascularized and potentially difficult to differentiate. DWI in liver MRI has been shown to be helpful in the classification of liver lesions, although with a substantial ADC-values-overlap. First results suggest that IVIM allows for improved characterization of liver lesions. In this study we evaluated IVIM-derived parameters in HCC and FNH with two different MR-scanners. - Material and methods - 72 patients (29 FNH, 43HCC) were examined prospectively using two 1.5 T-MRI scanners (Aera/MagnetomAvanto, Siemens, Germany). Quantitative analysis of IVIM-derived parameters and ADC800-values was performed independently by two radiologists. The concordance between the reviewers was tested using a Pearson-/Spearman-correlation. The mean values for significant differences between FNHs and HCCs and between the two MR scanners were compared using a two-tailed t-test/Mann-Whitney-U test. An ROC analysis assessing the diagnostic performance of the parameters was performed. - Results - The concordance between the two f-, D- and D*-measurements were r=0.81, 0.81 and 0.84, and r=0.58 for ADC-values. D-values and ADC800-values were significantly lower in HCC compared to FNH (p<0.001), there was no significant difference for f and D*. D had the largest AUC (0.76) for the differentiation between the two entities. Most parameters were not significantly different between the two MRIs. - Conclusion - IVIM-derived D and ADC are comparable for the differentiation between HCC and FNH. Since ADC-measurement means less effort than IVIM, ADC should be used for the differentiation between the two entities. Furthermore, quantitative results obtained from different scanners match closely.
Gesehen am 13.05.2020